Risks and Opportunities of the Digital Transformation of Occupational Health and Safety in the Republic of Croatia – Impact on Company Operations - Katić, Tomislav; Krivec, Jana; Palačić, Darko (Global journal of Business and Integral Security, 2026)
Occupational health and safety management (OHS), as a secondary business process, is part of all work processes of a business organization. If a company implements a digital transformation of its business, an integral part of this must be the digitalization of OHS management process. Although at first glance it can be concluded that companies in the Republic of Croatia lag behind European and global companies in terms of the digitalization of OHS processes, there are certainly positive examples. The first part of the paper presents the theoretical assumptions of digitalization and OHS and the previous research in this area. The second part of the paper provides an overview of the results of the most significant analyses and research on the impact of digital transformation on the OHS management system in the Republic of Croatia. The risks and opportunities of the digital transformation of this process are analyzed. The discussion and conclusion provide recommendations for improving the management of risks and opportunities of the digitalization of the occupational health and safety management system and its impact on company operations.